Talent magnet : how to attract and keep the best people - Miller, Mark, 1959- (Oakland : Berrett-Koehler Publishers, 2018)
'There is a long-standing truth in the world of organizations: talent wins! But how do you attract the best people? What do they really want? Based on his rigorous and extensive research, Mark Miller learned that top performers are looking for very different things than solid contributors. In Talent Magnet, Miller uses a clever and entertaining business fable to share these findings. He tells the parallel stories of Blake Brown, a CEO struggling with winning the war for talent, and Blake's sixteen-year-old son Clint, who is trying to get his first job so he can raise money to buy a well for a village in Africa. Blake reaches out to leaders in other industries and works with his team to solve the puzzle of making his organization a destination for exceptional performers. But he also learns from his son. Listening to Clint and his friends compare notes on the companies they've worked for that summer, ranging from the awful to the inspirational, Blake realizes they want the same three things out of a job as any top performer in a Fortune 500 company. Miller identifies these three critical aspects of a true talent magnet and explores the deeper meaning of each. He pulls back the curtain on what leaders can do to find and retain the very best people--a strategic need every leader faces'--
'There is a long-standing truth in the world of organizations: talent wins! But how do you attract the best people? What do they really want? Based on his rigorous and extensive research, Mark Miller learned that top performers are looking for very different things than solid contributors. In Talent Magnet, Miller uses a clever and entertaining business fable to share these findings. He tells the parallel stories of Blake Brown, a CEO struggling with winning the war for talent, and Blake's sixteen-year-old son Clint, who is trying to get his first job so he can raise money to buy a well for a village in Africa. Blake reaches out to leaders in other industries and works with his team to solve the puzzle of making his organization a destination for exceptional performers. But he also learns from his son. Listening to Clint and his friends compare notes on the companies they've worked for that summer, ranging from the awful to the inspirational, Blake realizes they want the same three things out of a job as any top performer in a Fortune 500 company. Miller identifies these three critical aspects of a true talent magnet and explores the deeper meaning of each. He pulls back the curtain on what leaders can do to find and retain the very best people--a strategic need every leader faces'--
Keywords: Employees -- Recruiting; Ability; Success in business